English Language Teaching (ELT) for Special Needs Learners: Strategies and Challenges for Hearing Impairments Students - Fitria, Tira Nur (Teaching English as Foreign Language, Literature and Linguisticss, 2025)
This research describes the strategies and challenges of ELT for special needs learners, especially hearing-impaired students. This study employs a library research method. Teaching English to students with hearing impairments requires adaptive strategies that focus on visual-based methods, assistive technology, and inclusive practices. Key approaches include using images, videos, and written text, incorporating sign language, emphasizing reading and writing skills, and using assistive tools like subtitled videos and speech-to-text software. Teaching methods should be flexible, incorporating multimedia content, alternative communication tools, and collaborative learning to enhance engagement. Continuous reinforcement through repetition and an inclusive classroom environment further supports learning. Different strategies are used across language skills. Vocabulary instruction benefits from direct instruction, drilling, outdoor activities, and translation, though challenges like passive participation and time constraints persist. Visual scaffolding, repetition, gestures, and pictorial dictionaries aid comprehension, while game-based learning enhances vocabulary retention. Reading strategies integrate text with pictures, visual aids, and personalized approaches, incorporating sociocultural contexts for better engagement. Writing instruction relies on repetition, discussion, and guided writing, though interactive strategies like peer teaching and dramatization are underutilized. Speaking instruction follows structured lesson planning, using visual media and written reinforcement to support articulation and comprehension. Teachers face difficulties in teaching English to hearing-impaired students due to limited training, resources, and sign language skills. Students often lack support, making pronunciation, vocabulary, and comprehension harder. The absence of interpreters, emotional challenges, and weak parental and institutional support worsen the problem. Digital tools, visual media, and structured training are needed to improve instruction.